Pharmacokinetics of a Fixed-Dose Combination Product of Dapagliflozin and Linagliptin and Its Comparison with Co-Administration of Individual Tablets in Healthy Humans - Jin-Woo Park; Jong-Min Kim; Ji Hyeon Noh; Kyoung-Ah Kim; Hyewon Chung; EunJi Kim; Minja Kang; Ji-Young Park (MDPI AG, 2022)
Dapagliflozin, a selective sodium-glucose co-transporter-2 inhibitor, and linagliptin, a competitive, reversible dipeptidyl peptidase-4 inhibitor, are commonly prescribed antidiabetic medications in general clinics. Since there are several merits to combining them in a fixed-dose combination product, this study investigated the pharmacokinetic equivalence between the individual component (IC) and fixed-combination drug product (FCDP) forms of dapagliflozin and linagliptin. A randomized, open-label, single-dose crossover study was conducted. All participants (n = 48) were randomly allocated to group A (period 1: ICs, period 2: FCDP) or group B (period 1: FCDP, period 2: ICs), and each group received either a single dose of IN-C009 (FCDP) or single doses of both dapagliflozin and linagliptin. There was no statistically significant difference found between the pharmacokinetic variables of FCDP and IC. The values of estimated geometric mean ratios and the 90% confidence interval for both maximum concentration and area under the plasma drug concentration-time curve were within the range of 0.8-1.25 for both dapagliflozin and linagliptin. The results of the clinical study demonstrated comparable pharmacokinetic characteristics between IC and FCDP forms of dapagliflozin and linagliptin. The combined use of dapagliflozin and linagliptin was safe and tolerable in both formulations.